2021
DOI: 10.1038/s41598-021-89294-1
|View full text |Cite
|
Sign up to set email alerts
|

A candidate gene identified in converting platycoside E to platycodin D from Platycodon grandiflorus by transcriptome and main metabolites analysis

Abstract: Platycodin D and platycoside E are two triterpenoid saponins in Platycodon grandiflorus, differing only by two glycosyl groups structurally. Studies have shown β-Glucosidase from bacteria can convert platycoside E to platycodin D, indicating the potential existence of similar enzymes in P. grandiflorus. An L9(34) orthogonal experiment was performed to establish a protocol for calli induction as follows: the optimal explant is stems with nodes and the optimum medium formula is MS + NAA 1.0 mg/L + 6-BA 0.5 mg/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…We previously obtained three candidate genes (CL4020.Contig1_ All, Unigene 1627_All, and Unigene7900_All; Su et al, 2021).…”
Section: Cloning and Analysis Of The β-Glucosidase Encoding Genementioning
confidence: 99%
See 3 more Smart Citations
“…We previously obtained three candidate genes (CL4020.Contig1_ All, Unigene 1627_All, and Unigene7900_All; Su et al, 2021).…”
Section: Cloning and Analysis Of The β-Glucosidase Encoding Genementioning
confidence: 99%
“…Studies have shown that the content of PE is higher in the leaves of P. grandiflorus than in other parts (Su et al, 2021;Yu et al, 2021). Therefore, we collected P. grandiflorus leaves at seven time points of the day and night from 6:00 am to 12:00 pm (at 3-h intervals) as samples for analysis.…”
Section: Analysis Of β-Glucosidase Diurnal Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in this study, using UPLC combined with QTOF-mass spectrometry analysis, 38 saponins were identified or tentatively characterized with four different parts, including the blanching process. Thus, considering the change in saponin content in these materials, along with the transformation in their structure, platycodin (major saponin in PG) pathways are examined in light of previous studies [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%